Costs, Benefits, and Tax-induced Distortions of Stock Option Plans - Rainer Niemann; Dirk Simons (Center for Economic Studies and ifo Institute (CESifo), 2002)
In recent years stock option plans (SOPs) have become an important component of managerial remuneration in most industrialized countries. Commonly accepted, corporate as well as individual taxes have a major impact on the costs of a SOP. In contrast, the tax influence on the benefits of a SOP remains widely unperceived. This article deals with both cost and benefit aspects simultaneously by integrating taxation into a principalagent model, where the agent is compensated in options. Deriving the optimal quantity of options to be granted and the optimal exercise price to be set, resulting profits for managers and shareholders can be quantified. Comparing the results in a tax-free world to the results taking into account different levels of taxation several tax-induced incentive distortions can be identified.
Keywords: 330; stock options; principal-agent; taxation